Dynamic relaxation modelling of braced bending active gridshells with rectangular sections. (15th May 2019) - Collins, Matt; Cosgrove, Tom
Highlights: A MATLAB implementation of 6 DoF elements in a Dynamic Relaxation (DR) algorithm. Applies a DR algorithm to bending active gridshells suitable for rectangular sections. Addresses impact of different bracing types. Addresses impact of different joint models. Abstract: Bending active gridshells are structures that involve sophisticated analysis, design and construction processes. Like shells generally, they can achieve large span to thickness ratios. The computational modelling of bending active gridshells will include, in general, both a form-finding stage and a subsequent stage analysing deformations and internal forces under imposed loads. The analysis of bending active gridshells using the dynamic relaxation method is well represented in the literature. This study examines the effects of different joint models and bracing systems on the stiffness of gridshells. The effect of two types of bracing on stiffness is compared. The effects of different joint models are also examined. The computational modelling is carried out by implementing the dynamic relaxation method in MATLAB and validated by reference to closed form benchmark solutions and previously validated finite element models. Significant variations in stiffness are observed for different bracing and joint models.